2007
DOI: 10.1002/jor.20393
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 gene polymorphisms in patients with osteonecrosis of the femoral head with and without cerebral white matter lesions

Abstract: Cerebral white matter lesions (WML) are present in more than 50% of patients with osteonecrosis of the femoral head (ONFH). Paraoxonase 1 (PON1) gene product is a detoxifying and pesticide metabolizing enzyme. Genetic variants of the PON1 gene have been found to influence the occurrence and progression of WML. We examined whether two PON1 polymorphisms (M55L and R192Q) are associated with ONFH and influence the occurrence of WML. We studied 104 patients with ONFH and 113 healthy age-and sex-matched subjects. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…These risk genes/polymorphisms are involved in a series of biological processes, including the regulation of cholesterol (e.g., ApoE, CETP) (Nebes et al, 2001;Hogh et al, 2007;Godin et al, 2009;Paternoster et al, Brought to you by | Carleton University OCUL Authenticated Download Date | 6/18/15 3:37 AM 2009; Qureischie et al, 2009), the regulation of systemic blood pressure and cerebral blood flow (e.g., ACE, AGT, AGTR1, CYP11B, F3) (Amar et al, 1998;Schmidt et al, 2001;Verpillat et al, 2001;Hassan et al, 2002;Henskens et al, 2005;van Rijn et al, 2007;Smith et al, 2009;), the biosynthesis of DNA and RNA (e.g., MTHFR) (Kohara et al, 2003;Linnebank et al, 2009;Hong et al, 2009;Szolnoki et al, 2012), immune response and inflammation (e.g., IL-6, IL5RA, ITGB6, CAPN10, NR3C1, KITLG) (Fornage et al, 2008;van Rossum et al, 2008;Smith et al, 2009;Fernandez-Cadenas et al, 2011), neuron regeneration (e.g., BDNF) (Taylor et al, 2008), neuroinflammation (e.g., MMP2, MMP3, MMP9, MMP13) (Fornage et al, 2007;Smith et al, 2009;Fernandez-Cadenas et al, 2011), cystoskeleton and cell adhesion (e.g., KNS2, ADD1, A2M, ICAM1) (van Rijn et al, 2006;Szolnoki et al, 2007;Fernandez-Cadenas et al, 2011;Fornage et al, 2011), and oxidative stress (e.g., PON1, NOS3) (Schmidt et al, 2000a;Henskens et al, 2005;Hadjigeorgiou et al, 2007;Fernandez-Cadenas et al, 2011). Although these risk genes/polymorphisms were shown to be strongly associated with the increased risk of LA, th...…”
Section: Candidate Gene Association Studymentioning
confidence: 99%
“…These risk genes/polymorphisms are involved in a series of biological processes, including the regulation of cholesterol (e.g., ApoE, CETP) (Nebes et al, 2001;Hogh et al, 2007;Godin et al, 2009;Paternoster et al, Brought to you by | Carleton University OCUL Authenticated Download Date | 6/18/15 3:37 AM 2009; Qureischie et al, 2009), the regulation of systemic blood pressure and cerebral blood flow (e.g., ACE, AGT, AGTR1, CYP11B, F3) (Amar et al, 1998;Schmidt et al, 2001;Verpillat et al, 2001;Hassan et al, 2002;Henskens et al, 2005;van Rijn et al, 2007;Smith et al, 2009;), the biosynthesis of DNA and RNA (e.g., MTHFR) (Kohara et al, 2003;Linnebank et al, 2009;Hong et al, 2009;Szolnoki et al, 2012), immune response and inflammation (e.g., IL-6, IL5RA, ITGB6, CAPN10, NR3C1, KITLG) (Fornage et al, 2008;van Rossum et al, 2008;Smith et al, 2009;Fernandez-Cadenas et al, 2011), neuron regeneration (e.g., BDNF) (Taylor et al, 2008), neuroinflammation (e.g., MMP2, MMP3, MMP9, MMP13) (Fornage et al, 2007;Smith et al, 2009;Fernandez-Cadenas et al, 2011), cystoskeleton and cell adhesion (e.g., KNS2, ADD1, A2M, ICAM1) (van Rijn et al, 2006;Szolnoki et al, 2007;Fernandez-Cadenas et al, 2011;Fornage et al, 2011), and oxidative stress (e.g., PON1, NOS3) (Schmidt et al, 2000a;Henskens et al, 2005;Hadjigeorgiou et al, 2007;Fernandez-Cadenas et al, 2011). Although these risk genes/polymorphisms were shown to be strongly associated with the increased risk of LA, th...…”
Section: Candidate Gene Association Studymentioning
confidence: 99%
“…The PON1-192QQ genotype was associated to increased risk for white matter lesions in Greek patients with osteonecrosis of the femoral head, while the PON1-55LM polymorphism was not associated with this pathology (Hadjigeorgiou et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches mainly focus on PON 192 and 55 polymorphisms, several trials found that they were associated with risk of ischemic vascular events as stroke and coronary heart disease [17]. One study also showed that PON-1 192QQ genotype increased risk for steroid-induced ONFH [18]. On the basis of these findings, we hypothesized that there might be a possible relationship between SNP of PON-1 and steroid-induced ONFH.…”
Section: Introductionmentioning
confidence: 94%